Demand information sharing in port concession arrangements. (August 2020) - Zheng, Shiyuan; Ge, Ying-En; Fu, Xiaowen; (Marco) Nie, Yu; Xie, Chi
Highlights: We investigate the effects of demand information sharing between PAs and POs on concession arrangements and market equilibria. We find that information sharing can improve welfare if its externality is sufficiently high. Absent compensation POs have no incentive to share their private information to PAs. With information sharing/payment arrangement and when ports cost and services are symmetric, one PO prefers to share information when the externality on welfare exceeds a threshold. Abstract: This paper investigates the effects of demand information sharing on concession arrangements and market equilibria, when two ports, each managed by a welfare-maximizing port authority and a profit-maximizing port operator, compete for demands. The problem is formulated as a multi-stage game, in which the authority and the operator at each port first decide whether to share demand information and make concession arrangements; then, the port operators compete à la Cournot. Alternative scenarios are compared to identify the effects of information sharing and market structure. Our analytical results identify the conditions under which demand information sharing is beneficial in port concession arrangements and highlight the importance of the underlying market structure and congestion levels in achieving these benefits. Specifically, we show that information sharing is a source of welfare improvement, and the effects are more significant when the positive externality of information sharing on welfare is large, inter-port competition is strong, and port congestion is costly. However, with no compensation, the port operators have no incentive to share their private information because otherwise, this is likely to increase concession unit-fees, limit their ability to compete effectively with each other, and ultimately reduce their expected profits. Therefore, transfer payments are necessary to encourage information sharing. With this arrangement and the assumed symmetric cost and service structure, we show that a port operator prefers sharing information if the externality of information sharing on welfare exceeds a threshold. Furthermore, when this externality is sufficiently large, the operators at both ports benefit from sharing information. Finally, when the two ports compete in price, we show that a port operator's single-side information sharing may not always benefit its port authority.